Current developments in West Africa's regional integration: Challenges for the future design of foreign and development policy - Klaus Grütjen (German Institute of Development and Sustainability (IDOS), 2024)
On 16 September 2023, Burkina Faso, Mali and Niger - all three states led by military regimes - decided to establish a new regional organisation, the Alliance of Sahel States (Alliance des Etats du Sahel - AES). This move was prompted by the worsening of the crisis within the Economic Community of West African States (ECOWAS) in 2023, a crisis that reached its peak to date with the announcement by the three AES members on 28 January 2024 of their withdrawal from ECOWAS, a regional organisation set up back in 1975. In a socio-political context in which the role and functions of the state, the extent of state powers and the way in which they are exercised are increasingly being called into question, new forms of political and social organisation are developing. These are also influenced by the current geopolitical developments in the changing world order. At the same time, states and societies and the ongoing regional integration processes are facing major new challenges. Within ECOWAS, conventional ideas of state and society, values and structures are coming up against growing tendencies towards a new understanding of statehood and sovereignty. In the West Africa/Sahel region, new processes of nation-building and state-building are under way, underpinned by efforts to renew social cohesion and to integrate the 'vital forces of the nation' - a concept cited increasingly frequently in these countries - as comprehensively as possible. These developments call for a realignment of German and European foreign and development policy. The political and social conditions and expectations of the partners in the West Africa/Sahel region are currently undergoing profound transformation. They need to be aligned with the content and interests of the value-based foreign policy advocated by Germany - in line with the principle of a 'partnership between equals'. Any appraisal of the future developments and integration of the dynamics that determine them must take account of the various integration processes, which are particularly diversified and run in parallel in this region. Adopting a comparative perspective, this paper provides an overview of the various regional organisations in the West Africa/Sahel region. It analyses the potential of each of them in terms of their development prospects and sustainability. In addition to the critical relationship between ECOWAS and the AES, it also examines the West African Economic and Monetary Union (WAEMU), the Integrated Develop-ment Authority of the Liptako-Gourma Region (Autorité de Liptako-Gourma - ALG) and the G5 Sahel, which is currently being dissolved. If the partnership between Germany and Europe on the one hand and the West African and Sahel states on the other is to be continued, it will be vital to adopt a pragmatic approach and maintain a political dialogue with all the partners. The states in this region are extremely important to Europe's future development. Moreover, it is only through communication based on mutual respect underpinning cooperation in the economic and development sectors that the growing influence of political powers such as Russia and Iran - whose ideas, interests and values are not in line with the Western Atlantic model of democracy governed by the rule of law - can be curbed effectively.
Keywords: 320; Sahel; ECOWAS; regional integration; autocracy; peace and security; Western Africa